Direct Observation of Doping Sites in Temperature‐Controlled, p‐Doped P3HT Thin Films by Conducting Atomic Force Microscopy. (24th July 2014) - Duong, Duc T.; Phan, Hung; Hanifi, David; Jo, Pil Sung; Nguyen, Thuc‐Quyen; Salleo, Alberto
<x xml:space="preserve">Abstract</x> The distribution of dopant sites in doped poly(3‐hexylthiophene) (P3HT) thin films is characterized using optical absorption, grazing‐incidence X‐ray diffraction, and conducting atomic force microscopy (c‐AFM). It is shown that dopant sites can be directly observed using c‐AFM and that the solution temperature dramatically impacts phase separation and conductivity in spin‐cast films. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>